Prevalence and associated factors of skin disease among school-age children of rural district of eastern zone of Tigray, Ethiopia, 2024 - Mulugeta Abraha Gebregiorgis; Almaz Berhe; Haftom Gebrehiwot; Mamush Gidey Abrha; Binyam Gebrehiwet Tesfay; Fiseha Abadi Gebreanenia; Binyam Tsegay Hagos; Willi Bahre; Guesh Teklu Woldemariam; Mearg Alemu Halefom; Tesfay Gebreslassie Gebrehiwot (PLoS ONE, 2026)
Background Skin diseases are conditions that affect the skin. Skin diseases encompass various conditions, including infections, allergies, inflammatory disorders, and infestation. Skin diseases are a significant public health concern, particularly among school-age children, as they can cause discomfort, and social stigma, and influence overall well-being. There is limited research conducted specifically among school-age children, especially in the postwar period, hindering the understanding of the extent of the problem and the identification of potential contributing factors. In Ethiopia, a study conducted on primary schoolchildren shows that the prevalence of skin diseases was 61.2%. Methods A school-based cross-sectional study was employed from September 10 to October 30, 2024, in selected schools of Eastern Tigray. A multi-stage sampling technique was used to choose Woredas and schools. Subsequently, 603 school-age children were recruited using systematic random sampling. Data were collected through interviewer-administered structured questionnaires and physical examination. Binary logistic regression was used to determine the strength of the association. Variables with a p-value <0.2 were selected for multivariable analysis, and a p-value <0.05 in the final model was considered statistically significant. Result The prevalence of skin disease among school-age children in the Rural District of the Eastern Zone was 411 (68.2%). Moreover, the factors associated with skin disease in this study were living in IDP (AOR = 2.96; 95% CI: 1.86–4.7), families with history of skin disease (AOR = 8.22; 95% CI: 5.19–13), sharing personal items (AOR = 3.89; 95% CI: 2.11–7.17), children who sometimes wash their hands before meals (AOR = 1.97; 95% CI: 0.99–3.89), and children who never wash their hands regularly (AOR = 4.93; 95% CI: 2.66–9.11). Conclusion The prevalence of skin disease among school-age children was high. Proper hand hygiene, not sharing personal items, and treating family members with skin diseases can help decrease the prevalence of skin diseases.